“Elixir forten” faz a gente viver bem: redes de cuidado e as experiências de crianças que vivem com HIV/Aids - Diniz, Jannine Jolanda Araújo (2016)
This dissertation aims to analyze the experiences and perceptions of children infected through vertical transmission, about the implications of living with HIV. This is a qualitative, exploratory and descriptive study, with individuals cared for in two SUS reference services in the treatment of AIDS located in the city of João Pessoa-PB, namely: Specialized Care Service (familiar SAE) in the Hospital Universitário Lauro Wanderley (HULW) and Complexo Hospitalar Clementino Fraga (CHCF). The development of the work took place in a period of one year and three months and included the participation of five families with children aged seven to eleven years old here understood as social networks, in the sense defined by Elizabeth Bott. This research was built out of an adaptation of the Daniel Bertaux‟s life stories method. The view of the children in this study have an important role because they act as interlocutors and are understood as agents able to produce, update and fill gaps on aspects related to their health condition. There is currently a growing interest in investigating children / childhood in the context of health, from their own looks, ideas and perspectives. However, the socio-anthropological studies on issues related to pediatric AIDS are still incipient. I argue that the children's answers reveal narrative fragments which represent significant social experiences, and it is essential also consider the individual characteristics, family and the broader socio-historical-cultural context in which the child participates. The life stories analyzed were told by many voices (polyphony) in order to have access to various points of view to better understand the issues investigated. The term "polyphony" is used in a meaning similar to that used by Clifford. The instruments used in the research were multiple, such as: in-depth interviews, in conversation format (dialogical method) with open questions; direct observation; production of drawings-stories with titles (free and thematic), various games, film and drama. The analysis of the results approached the thematic analysis proposed by Bardin, through which the following themes were organized: 1) Challenges of care social networks to HIV positive children; and, 2) Disease experiences of children living with HIV/AIDS. It was noted that while the literature emphasizes the diagnostic disclosure with children occurs another discovery, a progressive understanding of a condition that they have always been. Thus, knowledge about HIV / AIDS for them does not occur as a "biographic rupture," as described by Michael Bury, but as a read of clues.